2012
DOI: 10.1113/jphysiol.2011.226449
|View full text |Cite
|
Sign up to set email alerts
|

The resonant component of human physiological hand tremor is altered by slow voluntary movements

Abstract: Key points• Postural physiological hand tremor has a prominent component at ∼8 Hz unlike the associated EMG. Consequently, the gain between EMG and tremor is sharply peaked at ∼8 Hz.• Deduction and a simple model using pre-recorded EMG or random noise as an input show that the ∼8 Hz peak is a consequence of resonance.• During voluntary movement the gain peak enlarges and shifts to a lower frequency but the EMG spectrum shows no corresponding changes. This reflects muscle thixotropy. Adjustment of the muscle pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 37 publications
2
55
1
1
Order By: Relevance
“…Our data also tend to refute the hypothesis that physiological tremor, whether postural or kinetic, is exclusively mediated by peripheral and/or spinal mechanisms (Joyce and Rack, 1974;Lakie et al, 1986Lakie et al, , 2012Vernooij et al, 2013). This hypothesis posits that physiological tremor is either the consequence of broad-band forcing of a nonlinear, resonant system, and that synchronous central input is not required (Vernooij et al, 2013), or that it reflects frequency components in the band of the firing rates of last-recruited, large motor units (Christakos et al, 2006), or that local oscillatory reflex loops induce synchronous motor unit activity at the level of the spinal cord (Lippold, 1970;Christakos et al, 2006).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Our data also tend to refute the hypothesis that physiological tremor, whether postural or kinetic, is exclusively mediated by peripheral and/or spinal mechanisms (Joyce and Rack, 1974;Lakie et al, 1986Lakie et al, , 2012Vernooij et al, 2013). This hypothesis posits that physiological tremor is either the consequence of broad-band forcing of a nonlinear, resonant system, and that synchronous central input is not required (Vernooij et al, 2013), or that it reflects frequency components in the band of the firing rates of last-recruited, large motor units (Christakos et al, 2006), or that local oscillatory reflex loops induce synchronous motor unit activity at the level of the spinal cord (Lippold, 1970;Christakos et al, 2006).…”
Section: Discussioncontrasting
confidence: 49%
“…Several lines of evidence suggest that physiological tremor is secondary to central oscillatory activity (Conway et al, 1995;Vallbo, 1995a, b, 1996;Elble, 1996;Kakuda et al, 1999;Wessberg and Kakuda, 1999;Duval et al, 2000Duval et al, , 2005McAuley and Marsden, 2000;Gross et al, 2002;Evans and Baker, 2003;Jaberzadeh et al, 2003;Proudlock and Scott, 2003;Bye and Neilson, 2010). However, mechanical resonance of the limb alone has been shown to be sufficient to produce a characteristic physiological tremor spectrum (Vernooij et al, 2013), and it has been argued that the apparent motor unit synchronization and observations of corticomuscular coherence with tremor are epiphenomenal and a mere consequence of peripheral resonance (Lakie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This corresponded to the peak frequency of isotonic hand acceleration, leading the authors to conclude that the primary cause of tremor was the stretch reflex. However, a number of other studies have shown that the peak frequency of hand tremor does not match the peak frequency of the demodulated EMG (for example, Raethjen et al 2000;Timmer et al 1998), and this has been confirmed by recent studies on hand tremor from our laboratory (Lakie et al 2012;Reynolds and Lakie 2010). In the present study, we systematically examine physiological finger tremor when the finger is fixed or free to move.…”
mentioning
confidence: 75%
“…This has lead to a "bump" model which seeks to explain physiological tremor in terms of rhythmic central drive (Bye and Neilson 2010). However, in recent work on hand tremor we have observed that all of the characteristics of tremor and pulsation during movement can be satisfactorily reproduced by a resonator driven by a noisy EMG input (Lakie et al 2012). The evidence for relevant central oscillators is tenuous, and here we test the idea that the distinguishing features of physiological tremor do not require any central drive.…”
mentioning
confidence: 84%
See 1 more Smart Citation